Teori Kepemimpinan: Kajian dari Genetika sampai Skill - Nasib Tua Lumban Gaol (Benefit: Jurnal Manajemen dan Bisnis, 2020)
Leadership has been appeared since human to begin establishing a community in the world and it continuously grows further because of its usefulness. Particularly, the leadership is a pivotal aspect to increase the management process in any organization. However, it still needs to investigate deeply so that it can be understood comprehensively by practitioners and scholars. Consequently, the study is aimed to explore the history, theories, and basic concepts of leadership. Based on the literature review, it was revealed that leadership history can be traced based on its etymology and philosophy even though the topic of leadership had been known from the ancient age. Moreover, some leadership theories that influence its existence are genetic, great man, trait, behaviour, path-goal, contingency, transformational, and skill. Furthermore, leadership can be conceptualized as the leader’s personal ability to influence others (followers) through relationships, interactions, behaviours and credibility to attain the defined goals. Therefore, this study contributes to advance the leadership literature and emphasize its connection to the field of management. Further studies are recommended to investigate how leadership practices can improve the management process in the organization.